A quantitative review of relationships between ecosystem services - Lee, Heera; Lautenbach, Sven (Ecological indicators, 2016)
Ecosystems provide multiple ecosystem services (ES) to society. Ignoring the multi-functionality of land systems in natural resource management generates potential trade-offs with respect to the provisioning of ES. Understanding relationships between ES can therefore help to minimize undesired trade-offs and enhance synergies. The research on relationships between ES has recently gained increasing attention in the scientific community. However, a synthesis on existing knowledge and knowledge gaps is missing so far. We analyzed 67 case studies that studied 476 pairwise ES combinations. The relationships between these pairs of ES were classified into three categories: “trade-off”, “synergy” or “no-effect”. We tested three hypotheses: (1) a dominant relationship between ES exists for each ES pair; (2) this relationship is influenced by the scale at which the relationship had been studied as well as by the land system the analysis took place; and (3), this relationship is further affected by the method applied to characterize the relationship. For the first hypothesis, we demonstrated a comprehensive matrix of pairs of ES. Most pairs of ES (74%) had a clear association with one category: the majority of case studies reported similar relationships for pairs of ES. A synergistic relationship was dominant between different regulating services and between different cultural services, whereas the relationship between regulating and provisioning services was trade-off dominated. Increases in cultural services did not influence provisioning services (“no-effect”). For the second hypothesis, our analysis showed that the overall pattern of ES relationships did not change significantly with scale and land system archetypes except for some ES pairs. The regional scale was the most commonly considered, and case studies were biased among different land system archetypes, which might affect our ability to find the effect of scale or land system archetypes on the pattern of relationships. The analysis for the third hypothesis showed that the choice of methods used to determine the relationship had an effect on the direction of the relationship: studies that employed correlation coefficients showed an increased probability to identify no-effect relationships, whereas descriptive methods had a higher probability of identifying trade-offs. Our results provide helpful information of which services to include in ES assessments for the scientific community as well as for practitioners. Furthermore, they allow a first check if critical trade-offs and synergies have been considered in an analysis.
Gesehen am 06.12.2018